Determinan Penggunaan Metode Kontrasepsi Jangka Panjang (MKJP) pada Pasangan Usia Subur (PUS) Dimasa New Normal di Kabupaten Indragiri Hilir - Puspita Sari, Nila; Ikhtiyaruddin, Ikhtiyaruddin; Alamsyah, Agus (Jurnal Kesehatan Komunitas, 2023)
The long-term contraceptive method (MKJP) is a contraceptive used to delay, space out pregnancy, and stop fertility that is used long term, which includes IUD (Intra Uterine Device) Implant (KB) and steady contraception, while the new normal is a new order of life during the Covid-19 pandemic. The proportion of MKJP usage in Indragiri Hilir Regency (2019) was 9.97%, far below the national standard of 16.47% (Indragiri Hilir was the lowest achievement in the use of MKJP in Riau Province). The new normal during the COVID-19 pandemic with restrictions on community activities so that the intensity of husband-and-wife relations increases. The purpose of this study was to determine the determinants that affect the use of MKJP in Couples of Childbearing Age (EFA) in the new normal period. The results of this study are significant as evidence for policy determination in improving family planning programs in Riau Province. This type of research was quantitative analytic research using a cross-sectional study design. The location of this research is Indragiri Hilir Regency which has 20 sub-districts with 158 respondents. Data analysis using logistic regression. Results People with a negative attitude have a 3.11 times higher risk of not using the MKJP than people with a positive attitude. The statistical test showed significant results (p-value = 0.001 and 95% CI = 1.81-5.34). Those with low knowledge are at a 1.9 times higher risk of not using the Long-Term Contraceptive Method (MKJP) than those with good knowledge. The statistical test showed significant results (p-value = 0.016 and 95% CI = 1.13-3.22). The variable that was inversely related to the use of MKJP in Indragiri Hilir Regency was the officer's role variable with OR = 0.5 and Access to Family Planning Services OR = 0.26. The public health center must provide good communication on family planning services and supporting facilities, especially queues at the public health center so that people want to implement family planning.